2021
DOI: 10.3390/businesses1020006
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Responsiveness to a (Post)-Pandemic Grocery and Food Service E-Commerce Economy: An Exploratory Canadian Case Study

Abstract: The focus of this study looks at the motivations and rationale from a national survey of over 7200 Canadians in November 2020 into why they use online services to purchase food. As a result of the global COVID-19 pandemic, food supply chains have been significantly altered. Consumers are purchasing foods with different dynamics, including when they buy in-person at groceries, at restaurants or at food service establishments. Elements of the food supply chain will be permanently altered post-pandemic. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In this respect, a study of more than 1900 Chinese adult residents revealed that people preferred in-person to online shopping, although more than half of the studied population did at least one online or delivery order during the lockdown [ 15 ]. Moreover, in a large Canadian study, around 60% of the population used online retailing during the year 2020, either to do groceries or to buy from restaurants [ 16 ]. However, in an Italian study, only 9% of the population used online delivery during the pandemic [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, a study of more than 1900 Chinese adult residents revealed that people preferred in-person to online shopping, although more than half of the studied population did at least one online or delivery order during the lockdown [ 15 ]. Moreover, in a large Canadian study, around 60% of the population used online retailing during the year 2020, either to do groceries or to buy from restaurants [ 16 ]. However, in an Italian study, only 9% of the population used online delivery during the pandemic [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent case of Gorillas, an on-demand grocery delivery service that seized operations in Antwerp and Brussels after just one year, indicates there is currently still little room for disruption in the Flemish market. On the other hand, non-exclusive grocery retailers such as Amazon might be able to compete on prices through cross-subsidization with other product/service categories [ 71 ]. While they may have the financial backing to penetrate a closed market, their presence in the European groceries market is still marginal and completely non-existent in Flanders.…”
Section: Online Accessibility Of Foodmentioning
confidence: 99%
“…The changes include numerous new spending behaviors like panic buying and stockpiling at grocery stores as news about the severity of the COVID-19 virus started to surface ( Ben Hassen et al, 2021 , Islam et al, 2021 ; Sheth, 2020). New behaviors have emerged within product types, with a shift towards e-commerce and new channels of delivery, such as curbside pickup ( Charlebois et al, 2021 , Mohamad et al, 2020 , Unnikrishnan and Figliozzi, 2021 ). Finally, during the evolving pandemic there has been a shift from in-person spending towards remote engagement, both within spending categories (from dining-in to take-out) as well as across spending categories (less money spent on restaurants and commuting coupled with a shift towards more spending on improving homes and investing in home-offices) ( Ben Hassen et al, 2020 ; Chaudhary, 2020; Hong et al, 2021 , Sherman and Huth, 2020 ).…”
Section: Introductionmentioning
confidence: 99%